Protective Effect of Black Soybean-Whey Blended Protein on Duodenal Barrier Injury and Liver Injury in Rats - Xin SHU; Weihong MENG; Wenjing XIE; Dongjie ZHANG; Helin WANG; Tianxin FU; Kejin ZHUANG (Shipin gongye ke-ji)
To investigate the protective mechanism of black soybean-whey blended protein (B-WP) against duodenal barrier and liver injury in rats, the rats were fed with low, medium, and high doses of B-WP for 28 days. On the last day, they received an intraperitoneal injection of 2.5 mg/kg lipopolysaccharide (LPS). Enzyme-linked immunosorbent assay kits were used to detect the levels of malondialdehyde (MDA), superoxide dismutase (SOD), and glutathione (GSH) levels in the duodenal tissues. Western blot analysis was used to detect the protein expression levels of NF-κB p65, NF-κB p-p65, JAK2, and STAT3. Hematoxylin and eosin (HE) staining, enzyme-linked immunosorbent assay, and quantitative real-time PCR were used to detect liver tissue morphology, alanine transaminase (ALT) and aspartate transaminase (AST) levels, and mRNA expression of Toll-like receptor 4 (TLR4) and myeloid differentiation primary response protein 88 (MyD88) genes. The results showed that LPS induced duodenal oxidative stress, activated NF-κB/JAK2/STAT3 pathway, and caused liver injury, subsequently leading to duodenal barrier injury. Dietary intervention with low, medium, and high doses of B-WP regulated oxidative stress, with the medium dose showing the most significant effect (P<0.01), as evidenced by a 34.93% decrease in MDA content, a 61.16% increase in SOD activity, and a 48.48% increase in GSH content. Dietary intervention with different doses of B-WP could reduce the protein contents of NF-κB p65, NF-κB p-p65, JAK2 and STAT3, and the medium dose dietary intervention showed the best effect. The protein content of NF-κB p65, NF-κB p-p65, JAK2, and STAT3 significantly decreased by 35.06%, 42.53%, 45.88% and 44.32%, respectively (P<0.01). Furthermore, dietary intervention with B-WP at varying doses exhibited differential improvements in liver injury, with the medium-dose intervention exerting the most substantial effect (P<0.01). This was evidenced by a significant decrease in alanine ALT and AST levels by 47.07% and 41.79%, respectively, along with a reduction in TLR4 and MyD88 mRNA levels by 48.87% and 45.46%, respectively. In summary, the protective effects of B-WP against LPS-induced duodenal barrier injury are attributed to its regulation of oxidative stress, inhibition of the NF-κB/JAK2/STAT3 pathway activation, and amelioration of liver damage. Notably, the medium dose B-WP diet exhibits the most potent protective effects.